Public-Key Encryption with Tight Simulation-Based Selective-Opening Security. (16th August 2017) - Lyu, Lin; Liu, Shengli; Han, Shuai
Abstract: In a selective-opening, chosen-ciphertext attack (SO-CCA) against a public key encryption scheme (PKE scheme), a probabilistic polynomial time (PPT) adversary obtains a vector of challenge ciphertexts, has access to a decryption oracle, adaptively selects to open some of the challenge ciphertexts and sees the corresponding messages together with the random coins. The simulation-based, selective-opening security against chosen-ciphertext attacks (SIM-SO-CCA security) protects the security of the unopened messages in a semantic way, i.e. it requires that the output of the adversary can be simulated by a simulator who sees only the opened messages. In particular, all information that the adversary can get from the unopened messages can also be simulated from the opened messages alone by the simulator. All security proofs of the available PKEs achieving SIM-SO-CCA security are not tight, and the security loss depends either on the number of challenge ciphertexts or on the number of decryption queries. In this work, we present the first PKE scheme which achieves SIM-SO-CCA security with a tight reduction to standard assumptions . This partially solves the open problem proposed by Hofheinz in EuroCrypt 2012.